2020
DOI: 10.3389/fcell.2020.00688
|View full text |Cite
|
Sign up to set email alerts
|

The Construction and Analysis of ceRNA Network and Patterns of Immune Infiltration in Colon Adenocarcinoma Metastasis

Abstract: Background: Colon adenocarcinoma (COAD) is a malignant and lethal tumor in digestive system and distance metastasis lead to poor prognosis. The metastasisspecific ceRNAs (competitive endogenous RNAs) and tumor-infiltrating immune cells might associate with tumor prognosis and distance metastasis. Nonetheless, few studies have concentrated on ceRNAs and Immune cells in COAD. Methods: The gene expression profile and clinical information of COAD were downloaded from TCGA and divided into two groups: primary tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 73 publications
(74 reference statements)
0
29
0
Order By: Relevance
“…Subsequently, the CIBERSORT algorithm performed deconvolution analysis on the immune microenvironment to assess the proportion of the immune cells in AD. What is more, previous research confirmed the effectiveness of the CIBERSORT technique (Dai et al, 2018;Mao et al, 2018;Chang et al, 2020). Besides, the immune cell infiltration scoring model was built by LASSO regression based on 22 immune cells.…”
Section: Discussionmentioning
confidence: 73%
“…Subsequently, the CIBERSORT algorithm performed deconvolution analysis on the immune microenvironment to assess the proportion of the immune cells in AD. What is more, previous research confirmed the effectiveness of the CIBERSORT technique (Dai et al, 2018;Mao et al, 2018;Chang et al, 2020). Besides, the immune cell infiltration scoring model was built by LASSO regression based on 22 immune cells.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies have performed hypoxia-related analyses for certain types of cancer, while constructing prognostic signatures, including hepatocellular carcinoma (Jiang et al, 2020), gastric cancer (Chen et al, 2020), and melanoma (Shou et al, 2020). In terms of COAD itself, many previous studies have also proposed transcriptome signatures associated with COAD prognosis through bioinformatics analysis (Chang et al, 2020;Di et al, 2020;Luo et al, 2020). Currently, there are several hypoxia-related signatures that can predict clinical outcomes of colorectal cancer patients (Lee et al, 2019;Zou et al, 2019;Yang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In multiple cancers, Treg cells are associated with poor prognosis ( 32 ). Meanwhile, M0 macrophages may be related with the distant metastasis and prognosis of COAD ( 33 ). Macrophages M1 and activated memory CD4 + T cells were highly expressed in the low-risk group.…”
Section: Discussionmentioning
confidence: 99%